New opportunities for efficient N2 fixation by nanosheet photocatalysts. Issue 33 (10th August 2018) - Li, Hao; Mao, Chengliang; Shang, Huan; Yang, Zhiping; Ai, Zhihui; Zhang, Lizhi
Abstract : Catalytic ammonia synthesis from dinitrogen (N2 ) under mild conditions has been considered to be the "holy grail" of N2 fixation, which is one of the most important chemical processes in the agriculture, biological and industrial fields. Abstract : Catalytic ammonia synthesis from dinitrogen (N2 ) under mild conditions has been considered to be the "holy grail" of N2 fixation, which is one of the most important chemical processes in the agriculture, biological and industrial fields. Given that current artificial N2 fixation is still dominated by the energy-intensive Haber–Bosch process, solar N2 fixation represents an encouraging and fascinating route for carbon-free and energy-saving N2 fixation. However, its practical application is seriously hampered by surface sluggish reaction kinetics. In this minireview, we share our perspectives on the use of two-dimensional (2D) nanosheets for the manipulation of photocatalytic N2 fixation. Nanosheet photocatalysts serve as the perfect platform for the engineering of surface active sites, including defects and iron, all of which can not only bolster photon–exciton interaction toward robust charge carriers generation upon light absorption, but also mimic the function schemes of MoFe-cofactor in nitrogenase toward sufficient N2 binding and activation. These merits endowed by nanosheets photocatalysts provide instructive information on exploring the rich nitrogen photochemistry on solid surfaces and offer new opportunities for the design of novel photocatalysts towards efficient N2 fixation.